Common and unique testosterone and 17 beta-estradiol degradation mechanisms in Comamonas testosteroni JLU460ET by transcriptome analysis - Wang, Ze; Chen, Mingming; Liu, Na; Zhao, Yongkang; Ru, Jintao; Qin, Chuanyu; Zhang, Tingdi (Frontiers in Microbiology, 2023)
Strain C. testosteroni JLU460ET was isolated for testosterone and 17 beta-estradiol degradation by our group. In this work, strain C. testosteroni JLU460ET was induced by testosterone and 17 beta-estradiol and then subjected to transcriptome analysis. There were 2047 upregulated genes after 3 hours of testosterone induction, 2040 upregulated genes after 13 hours of testosterone induction, 2078 upregulated genes after 3 hours of 17 beta-estradiol induction, and 2095 upregulated genes after 13 hours of 17 beta-estradiol induction. Significantly upregulated genes were mainly involved in steroid and aromatic compound degradation. A 100 kb steroid-degrading gene cluster was found by transcriptome analysis, which included 92 annotated genes and 58 novel genes. Among them, MucB/RseB and Fiu are secretory proteins for sensing substrates in the environment. MFS-1 and TonB are transporters for the transport of testosterone and 17 beta-estradiol. Ring-cleavage enzymes and beta-oxidation enzymes are important for degradation. The genes upregulated by both substrates were almost the same, but the degree of induction by testosterone was higher than that by 17 betaestradiol. Nine upregulated genes were selected for verification by quantitative realtime polymerase chain reaction (qRT-PCR). The qRT-PCR results were consistent with the transcriptome sequencing results. In this study, the common and unique metabolic mechanisms of testosterone and 17 beta-estradiol were compared by transcriptome analysis in C. testosteroni JLU460ET for the first time.